Pengaruh Kepercayaan Diri Dan Keterampilan Komunikasi Terhadap Public speaking Mahasiswa Prodi Administrasi Perkantoran Stambuk 2021 Universitas Negeri Medan - Nura, Alfi; Situmorang, Mita Rosalina (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
The purpose of this study was conducted to determine whether self-confidence partially affects the Public speaking of students of Office Administration Education Study Program Stambuk 2021, whether communication skills partially affect the Public speaking of students of Office Administration Education Study Program Stambuk 2021, and whether self-confidence and communication skills simultaneously affect the Public speaking of students of Office Administration Education Study Program Stambuk 2021 Medan State University. This type of research is ex post facto with a quantitative approach. The research population is all students of Office Administration Education Study Program Stambuk 2021, totaling 85 people from two classes with total sampling technique. Data collection with initial observations, questionnaires, and documentation. The results showed that there was a significant influence between self-confidence and communication skills on Public speaking of Office Administration Education Students Stambuk 2021 Medan State University by 82.2%, while 17.8% was explained by other variables not included in this study